Management of posterior malleolus fractures: A multicentre cohort study in the United Kingdom. Issue 6 (August 2021) - Stringfellow, T.D.; Walters, S.T.; Nash, W.; Ahluwalia, R.; ,
Highlights: Often due to low energy trauma, present to all hospitals, trauma centres and units. In the UK, pre-operative CT scanning is under-utilised in these complex fractures. Radiographs under-represent fragment size and fracture anatomy compared with CT. Syndesmotic stabilisation is often not required after posterior malleolus fixation. CT scanning should be performed in all cases, except for small avulsion fragments. Abstract: Background: There is a need to assess clinical practice in light of increasing literature recommending fixation of posterior malleolus (PM) fractures. This multicentre study examines treatment approaches, within both Major Trauma Centres and District General Hospitals and role of radiographs and CT scanning. Methods: Trauma lists and databases were used to identify patients and data collected from electronic and paper medical records and imaging systems between August 2017−18. Analysis of treatment and outcomes was then conducted. Results: One-hundred-and-sixty ankle fractures were included in the study, only 68 ankle fractures underwent CT scanning following initial radiographs and of these, 65 were managed operatively, with 32 undergoing PM fixation. Syndesmotic stabilisation was performed in 9.6% where the PM was fixed. Conclusion: CT is still under-utilised, PM fractures that appear to be anything other than small avulsion-type injuries should undergo CT scanning. Syndesmotic stabilisation is statistically less likely to be performed with fixation of the PM.